Outcomes of patients admitted with acute coronary syndrome to a district level hospital in a lower to middle income country - Govender, Kamini (Department of Medicine, 2025)
Background: Acute coronary syndrome (ACS) has become a leading cause of death in low-and middle-income countries. There is a lack of data regarding the outcomes of ACS in Africa. This study aims to assess the outcomes of ACS patients admitted to a resource-limited district hospital in Cape Town, South Africa. Methods: We conducted a retrospective observational study of patients admitted with ACS to the Department of Medicine at Victoria Hospital, Cape Town, from the 1 st September 2020 to 30 November 2020. Results: Eighty eight patients with a diagnosis of ACS was admitted, of who 52 had NSTEMI/UAP and 36 patients had STEMI. The median age was 60 years, with a male predominance of 61.36%. The major risk factors for CAD were hypertension and smoking. The overall 1-month, 6-month, and 12-month mortality rates for our cohort were 4%, 17%, and 19%, respectively. Patients that received coronary intervention (thrombolytics/PCI/CABG) had better outcomes than in those who were managed conservatively. Conclusion: This study describes the experience of ACS management in a resource-limited public hospital in Cape Town, South Africa. Our patients had multiple cardiovascular risk factors with a higher mortality than published data. The lack of receiving coronary intervention was associated with worse outcomes.